Persepsi Guru Pendidikan Agama Islam Terhadap Implementasi Kecerdasan Buatan (AI) Dalam Proses Pembelajaran - Sudirman, Sudirman; Intan Kumalasari; Taufiq Hidayat siregar; Susrianingsih; Leli Hasanah Lubis (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2025)
The development of artificial intelligence (AI) in the world of education opens up new opportunities as well as challenges, especially for Islamic Religious Education (PAI) teachers who must balance technological innovation with Islamic values. This study aims to analyze PAI teachers' perceptions of the implementation of AI in learning, with a focus on AI literacy, training needs, perceptual barriers, and attitudes towards AI. This study uses a quantitative approach with the PLS-SEM method and involves 80 PAI teachers in Labuhanbatu through a purposive sampling technique. The results show that AI literacy has a positive effect on training needs, which then has a significant impact on positive attitudes towards AI. Conversely, perceptual barriers have a negative impact on these attitudes. There is also an indirect effect between AI literacy and teacher attitudes through the mediation of training needs. This study emphasizes the importance of increasing AI literacy and relevant training to support the readiness of PAI teachers in utilizing AI effectively and in accordance with Islamic values